A Novel Method of Damage Control for Multiple Discontinuous Intestinal Injuries with Hemorrhagic Shock: A Controlled Experiment. Issue 5 (27th May 2020) - Wu, Weihang; Cai, Zhicong; Lin, Nan; Yang, Weijin; Hong, Jie; Lin, Li; Lin, Zhixiong; Song, Junchuan; Fang, Yongchao; Lin, Chen; Zhang, Hongwen; Chen, Dongsheng; et al.
Abstract: Aim: In this study, we examined the effects of branched silicon tube (BST) and temporary closed circle (TCC) in a Beagle dog model of multiple transection of small intestine and discontinuities suspected intestinal necrosis with hemorrhagic shock. Materials and Methods: Ten male Beagle dogs were randomly divided into two groups. Hemorrhagic shock was induced by bleeding. Intestine was severed. Suspected intestinal necrotic model by ligating the mesenteric vessels was established, with a small tertiary mesenteric vessel reserved. Fracted intestines were ligated (IL group, n = 5) or reconnected with BST (IR group, n = 5). The abdominal cavity was temporarily closed with TCC. Definitive surgery was conducted after 24 h. Results: There was no statistical difference between two groups in the weight of dogs, their blood loss, fluid resuscitation, operation time of early emergency treatment (EET). After definitive surgery, all dogs in IR group and 3 dogs in IL groups were alive. 18 (90%) suspicious necrotic intestinal segments in IL group became necrotic, but 20 (80%) segments in IR group didn't develop obvious changes ( p <  0.01). From 2 h after EET, the endotoxin concentration in IL group was significantly higher than that in IR group (133.87 ± 43.73 vs. 56.31 ± 24.70 pg/ml, p <  0.01). Microscopic examination revealed that much more severe damage occurred in the suspicious necrotic intestinal segments in IL group. Conclusion: Both reconnecting intestine with BST and temporary abdominal closure with TCC are viable methods of damage control for multiple discontinuous intestinal injuries.